Effects of Fe on Oxidation of Ni-20Cr and Ni-30Cr Alloys at 800 °C in Wet CO2 Gas - Xie, Yun; Zhang, Jianqiang; Young, David J. (High temperature corrosion of materials, 2020)
The oxidation behaviour of model alloys Ni-(20, 30)Cr (wt.%) with (0, 1, 5, 15%) Fe was investigated at 800 °C in Ar-20%CO 2 -20%H 2 O gas. All 20Cr alloys developed a multilayered scale, and the outer scale layers on alloys containing iron were subject to spallation. However, all 30Cr alloys developed a scale which was predominantly chromia scale and resisted spallation. These effects are discussed in terms of Fe alloying effects on oxide scale development in the presence of water vapour. Differences between scaling behaviour in wet and dry CO 2 are shown to be explained by changed oxide transport properties.